Subclinical levels of anxiety but not depression are associated with planning performance in a large population-based sample. Issue 1 (6th September 2017) - Unterrainer, J. M.; Domschke, K.; Rahm, B.; Wiltink, J.; Schulz, A.; Pfeiffer, N.; Lackner, K. J.; Münzel, T.; Wild, P. S.; Beutel, M.
Abstract : Background: Major depression and anxiety disorders are known to negatively influence cognitive performance. Moreover, there is evidence for greater cognitive decline in older adults with generalized anxiety disorder. Except for clinical studies, complex executive planning functions and subclinical levels of anxiety have not been examined in a population-based sample with a broad age range. Methods: Planning performance was assessed using the Tower of London task in a population-based sample of 4240 participants aged 40–80 years from the Gutenberg Health Study (GHS) and related to self-reported anxiety and depression by means of multiple linear regression analysis. Results: Higher anxiety ratings were associated with lower planning performance ( β = −0.20; p < 0.0001) independent of age ( β = 0.03; p = 0.47). When directly comparing the predictive value of depression and anxiety on cognition, only anxiety attained significance ( β = −0.19; p = 0.0047), whereas depression did not ( β = −0.01; p = 0.71). Conclusions: Subclinical levels of anxiety but not of depression showed negative associations with cognitive functioning independent of age. Our results demonstrate that associations observed in clinical groups might differ from those in population-based samples, also with regard to the trajectory across the life span. Further studies are needed to uncover causal interrelations of anxiety and cognition, which have been proposed in the literature, in order to develop interventions aimed at reducing this negative affective state and to improve executive functioning.